2017
DOI: 10.1016/j.mri.2016.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of cine displacement encoding with stimulated echoes (DENSE) in human subjects

Abstract: Objectives To test the hypothesis that two-dimensional (2D) displacement encoding via stimulated echoes (DENSE) is a reproducible technique for the depiction of segmental myocardial motion in human subjects. Materials and methods Following the approval of the institutional review board (IRB), 17 healthy volunteers without documented history of cardiovascular disease were recruited. For each participant, 2D DENSE were performed twice (at different days) and the images were obtained at basal, midventricular an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 21 publications
1
30
0
Order By: Relevance
“…Regarding the choice to use circumferential rather than radial strain in this study, we have previously shown the superiority of DENSE circumferential strain over radial strain for the quantification of dyssynchrony, a parameter closely related to mechanical activation time. Also, it has been shown that cine DENSE assessment of circumferential strain is more reproducible than radial strain . Furthermore, the finding that circumferential strain performs well for this application makes physiologic sense based on the circumferential orientation of midwall myocardial fibers, as shown by diffusion tensor imaging in a canine model of dyssynchrony .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Regarding the choice to use circumferential rather than radial strain in this study, we have previously shown the superiority of DENSE circumferential strain over radial strain for the quantification of dyssynchrony, a parameter closely related to mechanical activation time. Also, it has been shown that cine DENSE assessment of circumferential strain is more reproducible than radial strain . Furthermore, the finding that circumferential strain performs well for this application makes physiologic sense based on the circumferential orientation of midwall myocardial fibers, as shown by diffusion tensor imaging in a canine model of dyssynchrony .…”
Section: Discussionmentioning
confidence: 97%
“…Also, it has been shown that cine DENSE assessment of circumferential strain is more reproducible than radial strain. 19,32 Furthermore, the finding that circumferential strain performs well for this application makes physiologic sense based on the circumferential orientation of midwall myocardial fibers, as shown by diffusion tensor imaging in a canine model of dyssynchrony. 33 Lastly, radial strain is particularly poorly suited for this application because HF-CRT patients often have dilated ventricles with decreased wall thickness.…”
Section: Circumferential Versus Radial Strainmentioning
confidence: 99%
See 1 more Smart Citation
“…; Lin et al. ), echo‐based studies are less clear concerning the type of metric used in computing myocardial strains. A number of echo‐based studies have described Lagrangian and Eulerian strain (Dandel et al.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, accurate and reproducible high-resolution MRI strain imaging with rapid analysis has been demonstrated for both preclinical and clinical applications (12, 13). …”
mentioning
confidence: 99%